Steccherinum fragile sp. nov. and S. subcollabens comb. nov. (Steccherinaceae, Polyporales), evidenced by morphological characters and phylogenetic analysis - Liu, Zhan-Bo; Dai, Yu-Cheng (Phytotaxa, 2021)
A new poroid wood-inhabiting fungus in the family Steccherinaceae, Steccherinum fragile sp. nov., is described and illustrated from China based on morphological and molecular evidence. The species was collected in Yunnan Province, growing on the ground and undersides of rotten angiosperm wood. S. fragile is characterized by an annual growth habit, resupinate basidiocarps with salmon to peach pores when fresh becoming cinnamon buff to pinkish buff upon drying, a thin margin with distinct rhizomorphs, a monomitic hyphal system, generative hyphae thin- to distinctly thick-walled with simple septa, neither amyloid nor cyanophilous. The phylogenetic analysis based on ITS + nLSU rDNA sequences shows that the new species belongs to Steccherinum, forming a monophyletic lineage with strong support (100% BS, 100% BP, 1.00 BPP). In addition, a new combination, S. subcollabens, is also proposed based on examination of its type material and phylogenetic analysis. Phylogenetically, Steccherinum fragile is closely related to S. amapaense and groups with S. subcollabens, S. formosanum and S. collabens. Both morphological and molecular characters confirm the placement of the new species and combination in Steccherinum.